Genotypic, grain morphological and locality variation in rice phytate content and phytase activity - Lee, H. H.; Bong, C. F. J.; Loh, S. P.; Sarbini, S. R.; Yiu, P. H. (College of Agriculture and Veterinary Medicine, United Arab Emirates University, 2014)
Phytate complexes in whole grain rice are indigestible by human but can be broken down by endogenous phytase enzyme. The inherent phytate content and phytase activity could influence the nutritional quality of whole grain rice. This work aims to determine and identify their variability with genotypes, growing areas and grain morphology. It was found that the whole rice grain was largely high in phytate content (18.20 to 32.36 g/kg) but low in phytase activity (4.77 to 102.65 U/kg), with significant variation among cultivars. Phytate content was marginally different between growing locations but, with no significant difference among their genotypes and grain morphology. This variation could be due to locality factors such as cropping and fertilization practices in the cultivation site. Meanwhile, phytase activity appeared to be determined by genotype, grain width and grain length-to-width ratio. A relatively high phytase activity could be selected from the whole grain rice based on rounded grain and in the genotypic category of L. These types of rice cultivars could reduce the inherent phytate level and improve the nutritional quality of the whole grain rice.